THE INFLUENCE OF ETHNOMATHEMATICS-CONTAINED PROBLEM BASED LEARNING MODEL AND MATHEMATICAL DISPOSITION SKILL TOWARD MATHEMATICAL REPRESENTATION - Rizkia, Sofri Amalia (Study Program of Mathematics Education University of Muhammadiyah Malang, 2017)
This research aims to: (1) knowing the positive influence ofethnomathematics-contained PBL model towards mathematicalrepresentation skill, (2) knowing the positive influence of mathematicaldisposition towards mathematical representation skill, and (3) knowing thepositive influence of ethnomathematics-contained PBL model andmathematical disposition skill towards mathematical representation. This isa quantitative research. Four classes in fifth semester from Educational ofElementary School students of 2016/2017 became the population of thisresearch. The sample in this research was Education of Elementary School2 (two) as the experiment class, and class of Educational of ElementarySchool 1 (one) as the control class. As for data collection, the used ofdocumentation, test, questionnaire, and observation technique was done tocomplete this research. The research analysis data was using SPSS 16,which is homogeneity test, normality test, simple regression test, and doubleregression test. The result showed that (1) there is positive influence ofethnomathematics-contained Problem Based Learning (PBI) model andmathematical disposition skill toward mathematical representation, (2) thereis positive influence of mathematical disposition towards mathematicalrepresentation skill, (3) there is positive influence of Problem BasedLearning (PBL) model and mathematical disposition skill towardmathematical representation.